Aliens and Man? : a Synopsis of Facts and Beliefs. - Kroth, Jerry (Algora Pub., 2010)
NASA astronauts and Soviet cosmonauts have said they saw?something,? Senator Dennis Kucinich famously said he believes UFOs are real, and just about everybody has heard rumors that the US military and intelligence agencies are?hiding something.? In this book, a college professor attempts to apply a dispassionate scientific approach to the question, pulling together and evaluating evidence for and against various theories about aliens from outer space and other unexplained phenomena. How real is the evidence, he asks, and what does it add up to?. This book is intended to present all the myste.